Atribut Halal Dan Atribut Produk Yang Mempengaruhi Niat Beli Produk Halal Di Kota Malang - Muhammad Firmansyah; Immanuel Mu'ammal; Sri Budi Cantika Yuli (At-Tadbir : jurnal ilmiah manajemen, 2023)
Products offered by manufacturers, especially imported ones, may contain unknown substances. This gives the impression to consumers that they have to be careful when choosing a product. This principle is carried out as a result of the creation of halal awareness in the community and the development of information on halal certification. The purpose of this study is to explain the elements that influence consumer purchase intentions for halal goods. Halal awareness, halal certification, product quality and advertising are examples of these aspects. This study uses a quantitative research methodology, using PLS-SEM data analysis. This study shows that halal awareness and halal certification have a beneficial and significant effect on customer buying interest in halal goods. This shows that the idea of halal is very important in product development because people are starting to recognize the value of halal products. Halal is more than a symbol; it is a broad concept that products are safe to eat, healthy, clean, and sanitary, to encourage consumer buying interest. Meanwhile, product quality and promotion do not show a significant relationship with purchase intention.